Exploring the Impact of Limited English Exposure on Language Proficiency Among Junior High School Students in Rural Areas - Handayani Samosir (TEKILA: Journal of Language Teaching and Literature, 2024)
Limited English exposure remains a significant barrier to language acquisition, particularly in rural educational settings where resources and opportunities for practice are scarce. This study explores the impact of limited English exposure on language proficiency among junior high school students in rural areas, focusing on SMPN 1 Kokoda, South Sorong Regency. Employing a quantitative methodology, the research examines a sample of 50 students from grades 7, 8, and 9, selected through purposive sampling based on varying levels of English exposure. Data were collected using a standardized English proficiency test, assessing listening, speaking, reading, and writing skills, alongside a questionnaire on English exposure outside the classroom. The analysis, conducted with SPSS software, includes descriptive statistics and correlation analysis to determine the relationship between English exposure and proficiency. The findings reveal that students generally perform better in reading compared to listening, speaking, and writing, with reading skills showing the highest mean score and writing the lowest. Correlation analysis indicates a positive and significant relationship between English exposure and proficiency across all skills, with reading exhibiting the strongest correlation (r = 0.67, p = 0.000). Students with daily exposure to English achieve higher proficiency levels, while those with rare exposure are predominantly in the low proficiency category. This underscores the crucial role of frequent English engagement in enhancing language skills. The study highlights significant challenges faced by rural students, including limited opportunities for English practice and exposure. The results suggest that increasing access to English through media, extracurricular activities, and daily practice could effectively bridge the proficiency gap in such contexts. This research provides valuable insights for educators and policymakers, emphasizing the need for targeted interventions to improve English proficiency in rural educational settings.